THE 21ST CENTURY MILIEU: LEARNING PREFERENCES OFMSU-TCTO SOPHOMORE STUDENTS - Colicol, Fernigil L. (Proceedings of the International Conference on Education, 2017)
The shift from teacher-centered to student-centered approach in the new milieu calls for teachers to adapt to the learners’ learning preferences. This study determined the levels of learning preferences of MSU-TCTO College of Education sophomore students along the different approaches and strategies in teaching, namely: Direct Instruction, Discussion, Indirect Instruction and Emerging Models of Teaching (EMT). It further determined if there were significant differencesin the students’ learning preferences between and amongthe variables tested. A descriptive research design was used. After a semester of exposure to the different teaching strategies and class activities, the 114 Educ. 121N (Social Dimensions of Education) sophomore students, 1st semester, AY 2016-2017, were given a teacher’s survey questionnaire. Findings revealedthat majority of the students “most preferred” the four teaching approaches, however, the EMThad thehighest mean and the direct instruction had the least. Students preferred most the feeding program,clothes-giving and parlor games activities – a community immersion, the cultural dance presentation and the role play activity of the EMT approach.Listening to a classmate’s report and to a teacher’s lecture under the direct instruction had the least overall mean. Among the four approaches, ANOVA showed a no significant difference in the students’ learning preferences. However, there was a significant difference in their levels of learning preferencesbetween direct and discussion, direct and indirect, and direct and EMT. In conclusion, the college students preferred collaborative, performance-based and hands-on learning.